The Role of Teacher–Student Relationships in Predicting Teachers’ Occupational Wellbeing, Emotional Exhaustion, and Enthusiasm - Cui, Liying (Frontiers in Psychology, 2022)
Wellbeing is regarded as a core dimension of an individual’s prosperity in the field of positive psychology. Underlying this multifaceted framework are emotive, mental, and societal forms of wellbeing, which can be based on constructive connections in the workplace. Career wellbeing among educators is linked to optimal mental functioning and their positive career experience is characterized in terms of the existence of constructive dimensions like enthusiasm at the workplace. Also, emotional exhaustion or fatigue is another central element in the research on educator burnout and it has an important effect on educators’ expert lives, alternatively, the excellence of teacher–student relationships is significant in the process of language learning. Due to the significant effect of the above-mentioned construct, this review tries to focus on the prominence of teacher–student relationships in this domain. The results from the review of the literature specified that high-value teacher–student relationships keep educators away from being emotionally exhausted since it can enhance the quantity of enthusiasm and lessen the amount of exhaustion. In a nutshell, this review of literature has suggestions for academics and experts in search of increasing teachers’ occupational wellbeing.